Working while enrolled in a university: Does it pay? - Iida Häkkinen (Uppsala University, Department of Economics, 2004)
Working while studying at university increases the time-to-degree and may interfere with learning, but the acquired work experience may also improve employment opportunities and increase wages after the graduation. This study examines how university students' employment decisions affect their labor market success after the graduation. The study is based on an individual panel data set of Finnish university students. The data set covers the years 1987-1998, which was a period of significant changes in the Finnish labor market. The study finds that in-school work experience increases graduates' earnings at the beginning of the career, but there are no statistically significant persistent effects on employment or earnings after controlling for the selection bias in work experience acquisition.
urn:nbn:se:uu:diva-4505
Keywords: I21; J24; J31; 330; university; in-school work; earnings; Studium; Nebentätigkeit; Arbeitsmarkt; Lohn; Finnland